Integration of Hydrogel Microparticles With Three-Dimensional Liver Progenitor Cell Spheroids - Gentile, Stefan D.; Kourouklis, Andreas P.; Ryoo, Hyeon; Underhill, Gregory H. (Frontiers in Bioengineering and Biotechnology, 2020)
The study of the liver progenitor cell microenvironment has demonstrated the important roles of both biochemical and biomechanical signals in regulating the progenitor cell functions that underlie liver morphogenesis and regeneration. While controllable two-dimensional in vitro culture systems have provided key insights into the effects of growth factors and extracellular matrix composition and mechanics on liver differentiation, it remains unclear how microenvironmental signals may differentially affect liver progenitor cell responses in a three-dimensional (3D) culture context. In addition, there has only been limited efforts to engineer 3D culture models of liver progenitor cells with the tunable presentation of microenvironmental stimuli. We present an in vitro model of 3D liver progenitor spheroidal cultures with integrated polyethylene glycol (PEG) hydrogel microparticles for the internal presentation of modular microenvironmental cues and the examination of the combinatorial effects with exogenous soluble factor. In particular, treatment with the growth factor TGF1 directs differentiation of the spheroidal liver progenitor cells to a biliary phenotype, a behavior which was further enhanced in the presence of hydrogel microparticles. We further demonstrate that surface modification of the hydrogel microparticles with heparin influences the behavior of liver progenitor cells towards biliary differentiation. Taken together, this liver progenitor cell culture system represents an approach for controlling the presentation of microenvironmental cues internalized within 3D spheroidal aggregate cultures. Overall, this strategy could be applied towards the engineering of instructive microenvironments that control stem and progenitor cell differentiation within a 3D context for tissue engineering, drug testing, and metabolic studies.